2020
DOI: 10.1074/jbc.ra120.012761
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analyses of the G729R 2-oxoadipate dehydrogenase genetic variant associated with a disorder of l-lysine metabolism

Abstract: 2-Oxoadipate dehydrogenase (E1a, also known as DHTKD1, dehydrogenase E1, and transketolase domain-containing protein 1) is a thiamin diphosphate-dependent enzyme and part of the 2-oxoadipate dehydrogenase complex (OADHc) in l-lysine catabolism. Genetic findings have linked mutations in the DHTKD1 gene to several metabolic disorders. These include α-aminoadipic and α-ketoadipic aciduria (AMOXAD), a rare disorder of l-lysine, l-hydroxylysine, and l-tryptophan catabolism, associated with clinical presentations su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…In comparison, the value of K d of 0.041 μM (for hE2o 1-173 di-domain) and K d of 0.060 μM (for E2o 144-386 core domain) were reported for hE1o (24), suggesting a different binding mode of hE1o and hE1a with the same hE2o component. Also in HDX-MS studies, it was demonstrated that the region from the N-terminal end of hE1a comprising residues 24-47 experienced significant protection from deuterium uptake in the sub-complex with hE2o, similarly to that observed for hE1o above (residues 27-40) (25). Importantly, two regions of hE1a comprising residues 485-518, which according to the recently reported X-ray structure (22) belong to the linker region connecting two halves of the hE1a monomer, and peptides in the C-terminal region of hE1a comprising residues 589-609, 646-664, and 847-874 experienced protection from deuterium uptake on interaction with hE2o (25).…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…In comparison, the value of K d of 0.041 μM (for hE2o 1-173 di-domain) and K d of 0.060 μM (for E2o 144-386 core domain) were reported for hE1o (24), suggesting a different binding mode of hE1o and hE1a with the same hE2o component. Also in HDX-MS studies, it was demonstrated that the region from the N-terminal end of hE1a comprising residues 24-47 experienced significant protection from deuterium uptake in the sub-complex with hE2o, similarly to that observed for hE1o above (residues 27-40) (25). Importantly, two regions of hE1a comprising residues 485-518, which according to the recently reported X-ray structure (22) belong to the linker region connecting two halves of the hE1a monomer, and peptides in the C-terminal region of hE1a comprising residues 589-609, 646-664, and 847-874 experienced protection from deuterium uptake on interaction with hE2o (25).…”
Section: Resultsmentioning
confidence: 81%
“…Also in HDX-MS studies, it was demonstrated that the region from the N-terminal end of hE1a comprising residues 24-47 experienced significant protection from deuterium uptake in the sub-complex with hE2o, similarly to that observed for hE1o above (residues 27-40) (25). Importantly, two regions of hE1a comprising residues 485-518, which according to the recently reported X-ray structure (22) belong to the linker region connecting two halves of the hE1a monomer, and peptides in the C-terminal region of hE1a comprising residues 589-609, 646-664, and 847-874 experienced protection from deuterium uptake on interaction with hE2o (25). To probe deep inside the assembly of hE1o and hE1a to E2o, we next turned to chemical cross-linking mass spectrometry (CL-MS) to identify loci of interaction in binary E1-E2 sub-complexes.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations